Transcriptional and Post-Transcriptional Regulations of Amyloid-β Precursor Protein (APP) mRNA - Sato, Kaoru; Takayama, Ken-ichi; Hashimoto, Makoto; Inoue, Satoshi (Frontiers in Aging, 2021)
Alzheimer’s disease (AD) is an age-associated neurodegenerative disorder characterized by progressive impairment of memory, thinking, behavior, and dementia. Based on ample evidence showing neurotoxicity of amyloid-β (Aβ) aggregates in AD, proteolytically derived from amyloid precursor protein (APP), it has been assumed that misfolding of Aβ plays a crucial role in the AD pathogenesis. Additionally, extra copies of the APP gene caused by chromosomal duplication in patients with Down syndrome can promote AD pathogenesis, indicating the pathological involvement of the APP gene dose in AD. Furthermore, increased APP expression due to locus duplication and promoter mutation of APP has been found in familial AD. Given this background, we aimed to summarize the mechanism underlying the upregulation of APP expression levels from a cutting-edge perspective. We first reviewed the literature relevant to this issue, specifically focusing on the transcriptional regulation of APP by transcription factors that bind to the promoter/enhancer regions. APP expression is also regulated by growth factors, cytokines, and hormones, such as androgen. We further evaluated the possible involvement of post-transcriptional regulators of APP in AD pathogenesis, such as RNA splicing factors. Indeed, alternative splicing isoforms of APP are proposed to be involved in the increased production of Aβ. Moreover, non-coding RNAs, including microRNAs, post-transcriptionally regulate the APP expression. Collectively, elucidation of the novel mechanisms underlying the upregulation of APP would lead to the development of clinical diagnosis and treatment of AD.